The End of History; an Investigation on the Future of History in View of Thinkers - Seyed Alireza Vasehee (تاریخ اسلام)
The prediction of "the future of history" or "the end of history" has been the center of attention of thinkers from long ago and it has faced them with this fundamental issue that supposing the purposefulness of history, which future is on the way of human being? Of course, this issue attracts the attention of the mass of people, but they overcome their need to some extent through optimism or affected by the prevalent traditions or the religious instructions as well as the prevalent culture, whereas thinkers won't easily communicate with that. This issue has been considered as the major concern during history, particularly when the difficulties of human life continued for a long time. From their viewpoint, the history could not be considered as an endless and aimless issue. Therefore, a number of thinkers decided to provide a comprehensive and meaningful interpretation from life to justify the minor and apparently human-created events in the light of it and to give the herald of human's life. This issue would not be possible except through the realization of a purposeful phenomenon. Consequently, in the last phases, particularly among western researchers, it has been done many debates in this regard. A great number of people who investigate this phenomenon are inspired by religious instructions but some thinkers focus on it from a philosophical view point. They attempt to find out the direction of history through identifying it as a reality and through which they try to open a window to look at the future in order to predict the perspective of human life. This writing is to investigate the view point of three philosophers of history such as Ibn e-Khaldun, Vico and Herder to show the future of history from their view point. Such investigations should be considered as primary studies to the perception of Mahdi's promised community resembling the bright future of humanity.